Atrial pacing to suppress ventricular arrhythmias in the critically ill patients: a case report. Issue 5 (16th April 2022) - Riad, Omar; Russell, Clare; Garfield, Ben; Behar, Jonathan M.
Abstract: Background: Atrial and ventricular arrhythmias are common in the critically ill due to a variety of factors including sepsis, myocardial ischaemia, renal dysfunction, and electrolyte disturbances. Anti-arrhythmic medications can be useful to control arrhythmias but can result in bradycardia and haemodynamic compromise. A paced atrial rhythm alongside normal atrioventricular conduction can be helpful to treat bradycardia, prevent arrhythmias, and support cardiac output. Case summary: A 55-year-old gentleman with pseudomonas pneumonia, respiratory failure necessitating mechanical haemodynamic support, and subsequent coronary ischaemia presented to the intensive care unit. Paroxysms of atrial fibrillation and ventricular arrhythmias caused haemodynamic embarrassment and presented an ongoing clinical challenge as anti-arrhythmic medications resulted in bradycardia and Torsade de Pointes. Atrial pacing mediated intrinsic conduction via the His-Purkinje system inhibited ventricular ectopy and further arrhythmia breaking the tachycardia—bradycardia cycle; this stabilized the patient, facilitated ongoing intensive therapy unit care and promoted recovery. Conclusion: Atrial pacing mediated intrinsic conduction via the His-Purkinje system is an effective approach to suppress ventricular ectopy and sustained arrhythmias whilst protecting the patient from haemodynamically compromising bradycardia.